Design contributions to the preparation of teaching materials suitable for children with ADHD - Pozza da Costa, Fernanda; Triska, Ricardo; Schmidt Alves Díaz Merino, Giselle (InfoDesign, 2024)
This article is inserted in context of teaching-learning of children with ADHD. Its objective was to propose guidelines for the development of teaching materials aimed at students with ADHD in the initial grades of elementary school. The study has an analytical nature and it was based on qualitative data obtained from a semi-structured interview with a psychopedagogue, a specialist in teaching and learning of children with neurodevelopmental and learning disorders. Data collection also involved the analysis of tests questions applied to a 7-year-old child with ADHD, a second-year elementary school student. The sample brought together 9 questions taken from school tests. Based on the information obtained, content analysis was conducted, crossing it with the adopted theoretical framework, which brought together the areas of Education and Design. The results include: the identification of characteristics of the analyzes teaching materials that do not contribute to the understanding of the content by children with ADHD; proposition of ten guidelines to the visual structuring of teaching materials that help directing students’ attentional focus. The study also identified opportunities for further research in the area.